Assessing the Impact of Multimedia-Based Tools on Early Language Acquisition Case of Third Year Pupils at the Primary School of Djoudi Youcef Benammar Souk Ahras - Riah Roumaissa (My University, 2024)
Abstract The purpose of the current experimental study is to demonstrate the impact of using multimedia tools on the early language acquisition process of third year pupils at the primary school of Djoudi Youcef Bennamar ,in Souk Ahras , to test the main hypotheses suggesting that multimedia tools usage improves and affects positively the early acquisition of the English language among pupils, two instruments were used : an experiment and an observation is conducted , the experiment is done to compare between two groups of 58 pupils of 3rd year to assess the efficacy of the usage and non-usage of multimedia tools and how it impacts their early acquisition of English language process, and the observation to investigate and analyze pupil’s interaction with the implication of these tools and how it impacts the process of learning, the obtained results confirmed the hypotheses established at the beginning of the study which proved that multimedia tools reflect positively on pupil’s early acquisition of English --------------------- الملخص الغرض من الدراسة التجريبية الحالية هو إظهار تأثير استخدام الأدوات المتعددة الوسائط على عملية اكتساب اللغة المبكر لدى تلاميذ السنة الثالثة في المدرسة الابتدائية جودي يوسف بن عمار في سوق أهراس، لاختبار الفرضيات الرئيسية التي تقترح أن استخدام الأدوات المتعددة الوسائط يحسن ويؤثر إيجابياً على اكتساب اللغة الإنجليزية المبكر بين التلاميذ. تم استخدام أداتين: تجربة وملاحظة. أُجريت التجربة لمقارنة مجموعتين من 58 تلميذاً في السنة الثالثة لتقييم فعالية استخدام وعدم استخدام الأدوات المتعددة الوسائط وكيف يؤثر ذلك على عملية اكتساب اللغة الإنجليزية المبكر، والملاحظة للتحقيق وتحليل تفاعل التلاميذ مع تطبيق هذه الأدوات وكيف يؤثر ذلك على عملية التعلم. أكدت النتائج التي تم الحصول عليها الفرضيات التي وُضعت في بداية الدراسة والتي أثبتت أن الأدوات المتعددة الوسائط تنعكس إيجابياً على اكتساب التلاميذ المبكر للغة الإنجليزية. ------------------------ Résumé L'objectif de la présente étude experimentale est de démontrer l'impact de l'utilisation d'outils multimédias sur le processus d'acquisition précoce du langage des élèves de troisième année de l'école primaire Djoudi Youcef Bennamar, à Souk Ahras. Pour tester les principales hypothèses suggérant que l'utilisation d'outils multimédias améliore et affecte positivement l'acquisition précoce de la langue anglaise chez les élèves, deux instruments ont été utilisés : une expérience et une observation ont été menées. L'expérience est réalisée pour comparer deux groupes de 58 élèves de troisième année afin d'évaluer l'efficacité de l'utilisation et de la non-utilisation d'outils multimédias et leur impact sur leur processus d'acquisition précoce de la langue anglaise. L'observation vise à étudier et à analyser l'interaction des élèves avec l'implication de ces outils et leur impact sur le processus d'apprentissage. Les résultats obtenus confirment les hypothèses établies au début de l'étude et prouvent que les outils multimédias ont un effet positif sur l'acquisition précoce de l'anglais par les élèves.